COST ACCOUNTING PERSPECTIVES ON PHARMACEUTICAL INVENTORY MANAGEMENT: EVALUATING FIFO IMPLEMENTATION AND DIGITAL RECORD-KEEPING IN COMMUNITY PHARMACIES - Nessa Maulidhyna (Universitas Tulungagung, 2025)
Effective pharmaceutical inventory management is essential for maintaining operational efficiency, controlling costs, and ensuring the sustainability of community pharmacies. Despite the widespread application of inventory control practices, many small pharmacies continue to rely on manual recording systems, which increase the risk of inventory inaccuracies, medicine expiration, and inefficient cost management. This study aims to analyze pharmaceutical inventory management from a cost accounting perspective by evaluating inventory recording practices, the implementation of the First-In, First-Out (FIFO) method, inventory control mechanisms, and the impact of supplier price fluctuations at Shegia Farma Community Pharmacy. A descriptive qualitative approach was employed using primary data collected through semi-structured interviews, direct observations, and documentary analysis of inventory records, purchase invoices, and stock reports. Data were analyzed using the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing, supported by methodological triangulation to enhance the credibility of the findings. The results indicate that routine inventory monitoring and consistent FIFO implementation have contributed to minimizing inventory obsolescence and improving inventory traceability. However, manual and spreadsheet-based recording systems remain vulnerable to data-entry errors, reporting delays, and limited real-time inventory visibility. Furthermore, supplier price fluctuations significantly affect procurement costs and profitability, highlighting the importance of effective cost control. This study contributes to the cost accounting literature by demonstrating that integrating FIFO, digital inventory recording, and systematic inventory control enhances financial accountability, operational efficiency, and sustainable pharmaceutical inventory management while supporting ethical business practices grounded in Islamic principles.